334 Phase Synchrony within the Right Prefrontal Cortex Predicts Severity of Major Depression. (1st April 2022) - Xiao, Jiayang; Myers, John; Metzger, Brian; Pirtle, Victoria; Mathura, Raissa; Allawala, Anusha; Adkinson, Joshua; Rey, Hernan; Goodman, Wayne; Pouratian, Nader; Bijanki, Kelly R.; Sheth, Sameer A.
Abstract : INTRODUCTION: Widespread alteration of brain networks has been observed in people with major depression. Although many conventional treatments are available, nearly one-third of patients could become treatment-resistant. Therefore, a clearer understanding of brain networks in depression is needed in order to develop more effective treatments. As part of an ongoing trial utilizing stereo-EEG (sEEG) intracranial recordings to inform deep brain stimulation (DBS) for treatment-resistant depression (TRD), we measured neural activity in the dorsolateral prefrontal cortex (dlPFC) and orbitofrontal cortex (OFC). METHODS: Treatment-resistant depression patients (n = 2) were implanted with frontotemporal sEEG electrodes and DBS leads in the ventral capsule/ventral striatum and sub-callosal cingulate. We acquired several measurements of depression severity throughout a 9-day inpatient monitoring period using the computerized adaptive test for depression inventory (CAT-DI). We measured connectivity using the phase locking value (PLV) between oscillations in the right dlPFC and OFC during resting state. Then we examined the relationship between depression severity and peak PLV within alpha band (8-12 Hz). RESULTS: We examined the connectivity between the deepest grey matter contact in the right dlPFC and in the right OFC. Peak PLV in alpha band was correlated with CAT-DI score under eyes-open condition in patient 1 and patient 2. CONCLUSION: Phase synchrony between right dlPFC and right OFC is involved in the severity of major depression. Increased dlPFC-OFC phase synchrony may relate to increased mood control or management.